Dramatic signs of place in contemporary classical shows: كاظم عمران موسى (Al-Academy, 2015)
(The sign) was born with the birth of man, after the primitive man revealed through it the forms of speech, to express his needs and instincts, and he expressed his insides through them, through the effect of his interaction and conflict with his human counterpart on the one hand and nature on the other hand, for the purpose of communicating and communicating information, as a primitive language Indicative ...., until the linguistic language replaced it and thus signs took a further development, represented by other means that were embodied by gestures, signs and movements that took common social formulas .. such as the dances that a person practiced in his social rituals and the objective and transitional movements they contained And gestures with intellectual and aesthetic connotations